2005
DOI: 10.1002/mds.20372
|View full text |Cite
|
Sign up to set email alerts
|

Differential pattern of hand‐tapping compromise in vascular versus idiopathic parkinsonism: A study based on computerized movement analysis

Abstract: We tested the characteristics and the differential pattern of upper extremity motor compromise, comparing hand tapping in patients with subcortical vascular encephalopathy (SVE; n = 18), idiopathic Parkinson's disease (PD; n = 18), and in healthy controls (n = 18). Both patient groups showed significant compromise in hand tapping compared with that in controls, with higher coefficients of variability (CV) regarding tapping amplitude and angular velocity, determined using a computerized movement analysis system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Bäzner et al analyzed the motor function of hands with tapping tests and showed significant differences comparing patients with PD, subcortical vascular encephalopathy and healthy controls [7]. It has been shown by Ünlü et al.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Bäzner et al analyzed the motor function of hands with tapping tests and showed significant differences comparing patients with PD, subcortical vascular encephalopathy and healthy controls [7]. It has been shown by Ünlü et al.…”
mentioning
confidence: 94%
“…Several studies used sensor systems to evaluate gait [3][4][5][6]13], hand motor function [7,8], or only single symptoms for lower and upper extremities [9][10][11][12]. However, a clinical examination, e.g.…”
mentioning
confidence: 99%
“…10,11 The clinical relevance of WMLs is controversial; however, recent data confirm the coexistence of vascular dementia, gait unsteadiness, and urinary incontinence subsumed in the syndrome of subcortical vascular encephalopathy (SVE) with severe WMLs. 12 There is growing evidence that the progression of WMLs is associated with progressive functional deficits such as gait disturbance 13 and upper limb discoordination, 14 and a large ongoing European trial 15 intends to clarify the issue of increasing disability in the elderly on the basis of progressive WMLs.…”
mentioning
confidence: 99%
“…Auch die Trennlinie zwischen einem VPS mit schleichendem Beginn und einer symptomatischen Parkinson-typischen Gangstörung bei SAE ist unscharf, da eine genauere Untersuchung oft auch bei klinisch dominierender Gangstörung diskrete Rigidität und Bradykinese der oberen Extremitäten zeigen kann [26].…”
Section: Differenzialdiagnoseunclassified